In the memory of the map : a cartographic memoir - Norment, Christopher (Sightline books., 2012)
Throughout his life, maps have been a source of imagination and wonder for Christopher Norment. Mesmerized by them since the age of eight or nine, he found himself courted and seduced by maps, which served functional and allegorical roles in showing him worlds that he might come to know and helping him understand worlds that he had already explored. Maps may have been the stuff of his dreams, but they sometimes drew him away from places where he should have remained firmly rooted. In the Memory of the Map explores the complex relationship among maps, memory, and experience - what might be.